Marcello Mastroianni (Pasquale) and Marina Vlady (Angela) in an orchard - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1954)
Days of Love tells the story of how two young peasants-- Angela (played by Marina Vlady) and Pasquale (played by Marcello Mastroianni)-- get married. Pasquale has just returned from military service and wants to marry his sweetheart, Angela.
Keywords: Italy -- Social life and customs -- 1945--- Drama; Marriage -- Italy -- Drama; Mastroianni, Marcello, 1924-1996; Motion picture actors and actresses -- Italy; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Stills (motion pictures); Vlady, Marina, 1938-